Evaluation of canal cleanliness of two rotary file systems with different taper systems: An in vitro scanning electron microscopic study - Sriram Ravi; Karthick Kumaravadivel; Sankar Vishwanath; Sebeena Mathew; Boopathi Thangavel; Deepa Natesan Thangaraj (Endodontology)
Aim: This study aims to compare and evaluate the amount of debris and smear layer remaining on the root canal walls prepared with TruNatomy and ProTaper Next files using scanning electron microscope (SEM). Methods: Sixty freshly extracted maxillary premolar teeth with a single root and oval canals were chosen, and decoronated to a standard length of 15 mm. Samples were randomly divided into three groups (n = 20) and instrumented. Group 1: ProTaper Next files (Dentsply Sirona) till X3, Group 2: Medium-size TruNatomy files (Dentsply Sirona), and Group 3: Gates Glidden drills and hand K files. 2 mL of 5.25% NaOCl was used between instruments. The final irrigation was done using 3 mL of 17% ethylenediaminetetraacetic acid and 3 mL of 5.25% NaOCl with passive ultrasonic agitation for 30 s. Samples were rinsed using distilled water, split mesiodistally, and evaluated under SEM The presence of superficial debris and a smear layer was evaluated using a standard scoring system. Data were statistically analyzed using the Kruskal–Wallis test and the post hoc Dunn’s test, with a level of significance set at P < 0.05. Results: None of the groups demonstrated complete debridement in all three-thirds of the root canal. In both experimental groups, a significant reduction in the amount of debris was seen, whereas there were no significant differences in the smear layer scores. Conclusion: Although ProTaper Next and TruNatomy files performed similarly, utilizing a lesser tapered file system with an optimal irrigation regimen would enhance the debridement ability without unnecessary removal of root dentinal structure.